Kualitas Pelayanan Surat Izin Mengemudi (SIM) Keliling oleh Direktorat Lalu Lintas Kepolisian Daerah Jawa Timur: (Studi Kasus: Lippo Plaza Sidoarjo) - Thalita Nadia Putri Aryanti; Meirinawati Meirinawati; Eva Hany Fanida; Neny Ayu Nourmanita (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
Quality public service represents a key measure of effective governance, including police administrative services. The Mobile Driving License (SIM Keliling) service is one of the public service innovations in the traffic sector designed to improve accessibility for the community. This study examines the quality of Mobile SIM services delivered by the Traffic Directorate of the East Java Regional Police at Lippo Plaza Sidoarjo. This research used a qualitative descriptive approach. Data collection techniques included observation, interviews with Mobile SIM officers and service users, and documentation. Service quality was analyzed using five dimensions proposed by Luke and Heyns (2020) reliability, responsiveness, assurance, empathy, and tangibles.The findings reveal that the Mobile SIM service generally performs well. Reliability is evident in the implementation of services in accordance with established procedures, although issues remain regarding service time certainty and transparency of administrative costs. Responsiveness is reflected in the officers’ prompt and attentive responses to public needs during the service process. Assurance is supported by officers’ professionalism, competence, and efforts to safeguard personal data, which enhance public trust. Empathy is demonstrated through friendly behavior, attention to individuals with special needs, and assistance throughout the service process. In terms of tangibles, the service location and main facilities are considered adequate; however, supporting facilities and officer identification still require improvement. In conclusion, while the Mobile SIM service fulfills most service quality indicators, further improvements are needed in time management, administrative transparency, and supporting facilities to achieve more optimal service quality.